Scaling the Heights : Social Inclusion and Sustainable Development in Himachal Pradesh - Das, Maitreyi Bordia; Kapoor-Mehta, Soumya; Tas, Emcet Oktay; Zumbyte, Ieva (World Bank, Washington, DC, 2015)
Himachal Pradesh has the reputation of being stable, inclusive, cohesive and well-governed and it stands apart in many respects from its neighbors in northern India. It has additionally, achieved remarkable growth, especially in the last two decades, which has been accompanied by very good human development outcomes. Despite being a predominantly rural society, educational attainment in Himachal Pradesh for instance, is among the best in the country; poverty headcount is nearly one-third of the national average; life expectancy is 3.4 years longer than the number of years an average Indian expects to live; and, per capita income is the second highest among "special category" states in India. Underlying its strong economic and social development outcomes is Himachal Pradesh's commitment to expand access to public services to the remotest areas, across tough, hilly terrain and its strong institutional foundations. Inter-group disparities are low in a state where traditionally disadvantaged groups such as the Scheduled Castes (SCs) and Scheduled Tribes (STs) make up a solid 30 percent of the population.